Constituency preferences and MP preferences: The electoral connection. (September 2020) - Martin, Danielle; Hug, Simon
The question how voter preferences relate to preferences of representatives under different electoral rules has attracted scholarly attention for some time. Although theoretical work suggests that proportional rule leads to more dispersion of representatives than plurality rule, empirical studies of this nexus have not yet reached a consensus. We argue that this is because they are plagued by serious problems as they rely on measures that differ for both sets of actors. We use behavioral data to estimate ideal points of voters and representatives on a common scale by taking advantage of the high frequency of referendums in Switzerland. We find that members of parliament elected in proportional representation systems are more widely dispersed around the median voter. Probing at what stage this difference in dispersion occurs, we also demonstrate this is the voters' doing, as it only applies to candidates who are elected.